The Effect Organizational Culture and Total Quality Management Practices in Secondary School Performance of Abu Dhabi - Alhosani, Khaled Sultan; Kamarul Bahari Bin Yaakub (European Journal of Multidisciplinary Studies, 2020)
The objective of this study was to investigate the effect of organizational culture and total quality management practices on secondary school performance in Abu Dhabi. Quantitative research design was adopted to obtain information from respondents. A total of 320 teachers were selected as a sample through the stratified random sampling method. Data analysis using structural equation modelling was used to determine the relationship between total quality management and secondary school performance.